The Problem of Developing Intellect and Creativity in the Student in Improving the Quality of Education in Study Activities (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study explores the intricate relationship between intelligence and creativity, addressing the existing gap in understanding their interplay and its implications for student development in higher education. Employing theoretical analysis and empirical evidence, the research examines convergent and divergent thinking models, psychological and social factors influencing creativity, and educational challenges faced by students. Findings indicate a nuanced interaction where creativity stems from high intelligence yet thrives on divergent thinking, highlighting adaptability and innovation as critical components of cognitive development. The results underscore the necessity of fostering both intelligence and creativity in educational strategies to enhance students' adaptive capabilities and professional success.